THE EFFECTIVENESS OF GENRE-BASED TASKS IN IMPROVING STUDENTS’ ACADEMIC WRITING SKILLS - Kalayo Hasibuan; Winda Nurhaliza; Endang Sri Ranti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic writing is one of the most challenging skills for students learning English as a foreign language. Many students experience difficulties in organizing ideas, using appropriate language features, and understanding the structure of academic texts. This study aims to investigate the effectiveness of genre-based tasks in improving students' academic writing skills. The research employed a quantitative approach using a pre-experimental design involving students enrolled in an academic writing course. Data were collected through pre-tests and post-tests and analyzed using descriptive and inferential statistics. The findings indicate that students showed significant improvement in their writing performance after participating in genre-based writing tasks. The improvement was evident in several aspects of writing, including organization, content development, grammar, vocabulary, and adherence to genre conventions. The results suggest that genre-based tasks provide learners with explicit guidance on text structure and language use, enabling them to produce more coherent and academically appropriate texts.